Gestão de riscos em processos administrativos em coordenações de curso de graduação: estudo de caso na Universidade Federal de Santa Maria - Martins, André Luiz Faverzani (2019)
This research aims to recommend actions to mitigate risks in administrative processes carried out by the coordination of undergraduate offices of the UFSM. As theoretical framework, aspects related to public governance and one of its mechanisms, risk management were presented, as well as aspects about organizational processes. As for the method, the research has analytical character, being classified as qualitative and quantitative, and in relation to its logic it is considered deductive. This is an applied research, using the case study method. Data were collected using the questionnaire adapted from Pôrto (2013), answered by 35 individuals. The 5W2H method was also applied to interviews with 10 individuals from the 35 respondents of the questionnaire in order to obtain data about the process functioning. In these interviews the risks related to the processes were also identified, following the order of risk management application defined in COSO IFES. For the data analysis, the other steps of COSO IFES were performed, classifying and identifying the risk response to support the elaboration of risk mitigation actions. The results showed that for the 27 risk events identified, 4 risks were classified as very high, 10 as high, 8 as moderate and 5 as low. It was possible to indicate as a response to the risk, the mitigation of 14 risks and the proposition of 12 actions to enable the mitigation of these risks. These actions include the promotion of strategies to reduce the failure rates in subjects, which enables the reduction of extra classes (besides the disproportionality of those with regular classes), the negative of registration due to lack of prerequisites and the conflict of schedules between subjects requested by students.